Sterile Injury Repair and Adhesion Formation at Serosal Surfaces - Zwicky, Simone N.; Stroka, Deborah; Zindel, Joel (Frontiers in Immunology, 2021)
Most multicellular organisms have a major body cavity containing vital organs. This cavity is lined by a mucosa-like serosal surface and filled with serous fluid which suspends many immune cells. Injuries affecting the major body cavity are potentially life-threatening. Here we summarize evidence that unique damage detection and repair mechanisms have evolved to ensure immediate and swift repair of injuries at serosal surfaces. Furthermore, thousands of patients undergo surgery within the abdominal and thoracic cavities each day. While these surgeries are potentially lifesaving, some patients will suffer complications due to inappropriate scar formation when wound healing at serosal surfaces runs awry. These scars called adhesions cause profound challenges for health care systems and patients. Therefore, reviewing the mechanisms of wound repair at serosal surfaces is of clinical importance. Serosal surfaces will be introduced with a short embryological and microanatomical perspective followed by a discussion of the mechanisms of damage recognition and initiation of sterile inflammation at serosal surfaces. Distinct immune cells populations are free floating within the coelomic (peritoneal) cavity and contribute towards damage recognition and initiation of wound repair. We will highlight the emerging role of resident cavity GATA6+ macrophages in repairing serosal injuries and compare serosal (mesothelial) injuries with injuries to the blood vessel walls. This allows to draw some parallels such as the critical role of the mesothelium in regulating fibrin deposition and how peritoneal macrophages can aggregate in a platelet-like fashion in response to sterile injury. Then, we discuss how serosal wound healing can run awry, causing internal scars called adhesions. Adhesions can cause significant morbidity in patients that underwent surgeries within body cavities. Current pathogenetic understanding of and potential future therapeutic avenues against adhesions are discussed.